EFEKTIVITAS MODEL PEMBELAJARAN RELATING, EXPERIENCING, APPLYING, COOPERATING, AND TRANSFERRING (REACT) DENGAN PENDEKATAN MATEMATIKA REALISTIK (PMR) TERHADAP LITERASI MATEMATIKA SISWA - Maulana, Mukhamad Riziq; Mariani, Scolastika; Wijayanti, Kristina (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Mathematical literacy is a very important ability that students must have because mathematical literacy supports students' mathematical abilities in many contexts that will be used in everyday life. This research aims to analyze the effectiveness of REACT learning with a realistik mathematics approach (PMR) on students' mathematical literacy. The method used in this research is quasi-experimental research with a pretest-posttest design. The sample used was students of Class IXA and IXB Mts Miftakhul Khoirot Branjang, Ungaran, Semarang Regency. The data used is the results of the mathematics literacy test before learning (pretest) and the results of the mathematics literacy test after learning (posttest). The data that has been collected is analyzed using statistical analysis in the form of a t-test, z-test, paired sample t-test, and N-gain test. The results of this research showed that the average value of students' mathematical literacy in the REACT learning model with PMR achieved minimum completeness, the proportion of students who achieved the average value in the REACT learning model with PMR was more than 75%, the average value of mathematical literacy in classes using the model REACT learning with PMR is higher than the average value of the class using the direct learning model, the increase in the average value of mathematics literacy for the class using the REACT learning model with PMR is higher than the increase in the average value of the class using the direct learning model. These results can be concluded that the REACT learning model with PMR is effective for students' mathematical literacy